Collective diffusion of charged nanoparticles in microchannel under electric field. (2nd February 2022) - Wang, Zhichao; Yu, Hongping; Liyanage, Achini; Qiu, Junjie; Thushara, Dilantha; Bao, Bo; Zhao, Shuangliang
Highlights: A microchip was developed to study the collective diffusion of nanoparticles. The collective and self-diffusion coefficient of nanoparticles were analyzed. The electric field governed the convection–diffusion of nanoparticles. The diffusion of nanoparticles can be enhanced or suppressed by electric field. Abstract: Controllable manipulation of the diffusion of nanoparticles through adopting external fields plays an important role in both separation and delivery of nanoparticles. This work demonstrates that external electric field can effectively enhance or suppress the collective diffusion of nanoparticles in microchannel. Collective diffusion coefficient of nanoparticles under positive or negative electric field was found to be 1.22 or 0.74 times that of the molecular collective diffusion coefficient without electric field applied, respectively. For the case of molecular collective diffusion, the collective diffusion coefficient is 5 times that of the self-diffusion coefficient. The deviation is attributed to the interparticle interactions among the multiple nanoparticles. Findings in this work can improve the understanding of readers for the collective diffusion of nanoparticles driven by concentration gradient under electric field. The phenomenon has great potential in the applications of separation and delivery of charged nanoparticles.